(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
This thesis describes in detail the strategic measures aimed at reducing unemployment in Uzbekistan, and also analyzes the practical measures taken in the country to eliminate this problem. Vocational training, entrepreneurship development, attracting foreign investment, social protection programs and agricultural modernization are indicated as the main ways to reduce unemployment. The official figures show that the creation of jobs, regulation of labor migration and attraction of foreign investments significantly reduce the level of unemployment.